2021
DOI: 10.3390/d13020078
|View full text |Cite
|
Sign up to set email alerts
|

Orchid Extinction over the Last 150 Years in the Czech Republic

Abstract: Understanding temporal changes in the distribution and abundance of various species is one of the key goals of conservation biology. During recent decades, the abundance and distribution of many species of plants and animals have declined dramatically, mainly because of habitat loss and fragmentation. The purpose of this study is to analyze the rate of extinction of orchids at various sites in different 20-year time intervals over the last 150 years, determined according to changes in society. Using the datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The need for effective conservation measures is urgently required for areas and countries that were affected by human activities in past decades, and thus have lost a part of their biodiversity or the distributions of certain species have been greatly reduced (Štípková and Kindlmann 2021;Štípková et al 2021b). It is commonly accepted that urbanization, land use changes and intensification of agriculture have resulted in a dramatic loss and fragmentation of habitats (Stewart 1992;Fischer and Stöcklin 1997;Kull et al 2002Kull et al , 2016Bilz et al 2011;Tsiftsis et al 2011).…”
Section: Orchids and Their Conservationmentioning
confidence: 99%
See 2 more Smart Citations
“…The need for effective conservation measures is urgently required for areas and countries that were affected by human activities in past decades, and thus have lost a part of their biodiversity or the distributions of certain species have been greatly reduced (Štípková and Kindlmann 2021;Štípková et al 2021b). It is commonly accepted that urbanization, land use changes and intensification of agriculture have resulted in a dramatic loss and fragmentation of habitats (Stewart 1992;Fischer and Stöcklin 1997;Kull et al 2002Kull et al , 2016Bilz et al 2011;Tsiftsis et al 2011).…”
Section: Orchids and Their Conservationmentioning
confidence: 99%
“…After 1948, small fields were consolidated into huge fields (Skaloš et al 2011) and subsidies for fertilizers were provided, which resulted in high levels of nutrient chemicals in the soil (Adams and Adams 1971). As a result, many orchids declined and can now only be found at a small number of sites (Štípková and Kindlmann 2021). After the change in regime in 1989, the subsidies for fertilizers ceased, which resulted for a while in a great decline in the use of fertilizers (Reif et al 2008).…”
Section: Orchids and Their Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have studied the species richness patterns of orchids in relation to the impact of climate change, and their conservation status on a regional or global scale [15][16][17][18][19][20][21]. For example, Huang et al [15], revealed the hotspots and species richness of Orchidaceae in China, including 1449 species, of which 97% were included in protected areas.…”
Section: Introductionmentioning
confidence: 99%
“…The need for taking effective conservation measures is urgently required for areas and countries that have been affected by human activities in the past decades, and thus have lost a part of their biodiversity or their species distributions have been largely diminished [11,12]. This is especially true in the case of Central European countries, which have been intensively affected by land use change or agricultural intensification [11].…”
Section: Introductionmentioning
confidence: 99%